The origins and development of the office of registrar in bankruptcy of the High Court. Issue 3 (11th December 2019) - Baister, Stephen; Tribe, John
Abstract: This article examines the history of the office of Bankruptcy Registrar of the High Court of England and Wales. It is argued that the power of the registrars to act judicially grew from their authorisation to act pursuant to delegated powers introduced in 1869 and that this began a major shift in their role from being largely administrative to their current status as fully fledged (and renamed) insolvency and companies court judges. The fluidity of bankruptcy offices in the nineteenth century is also examined, demonstrating that certain bankruptcy officer‐holders moved freely between functions in the course of the development in the office of registrar from what might be called its administrative phase to the judicial phase with the eventual creation of a Bankruptcy Court and more recently the creation of a specialist insolvency and companies list in the new Business and Property Courts. Finally, it is argued that a factor in the foregoing developments and the increasing reputation of the bankruptcy registrars was the extension of their jurisdiction from pure bankruptcy work to include company insolvency, directors' disqualification cases and non‐insolvency company work, a significant increase in their trial work and their acquisition of an appellate jurisdiction.